The Enhancement Quality of Squalene as a Marine Chemopreventive Agent and Vitamin A Level In The Shark Liver Oil at The Territorial Ocean of Cilacap - Yuhansyah Nurfauzi; Wahyu Kurniawan; Tusrianto Tusrianto (Indonesian Journal of Cancer Chemoprevention, 2011)
Recently, shark liver oil is developed as mainstay product for the Cilacap fishermen proceed to be traditional supplemental foods and health product that contains squalene and Vitamin A. Squalen is one of marine natural products has demonstrated proliferative activity in animal cancer studies and may have some radioprotective effects. This observation is aimed to enhance and improve squalene acquirement quality organolepthically. This observation uses experimental observation design. Shark liver in the bottle will be proceed by the tool that specially designed to produce shark liver oil. Its result is analyzed quantitatively to gain the squalene and vitamin A level. The comparison of squalene level that has been produced in this observation is approximately from 141 to 191 higher than standard squalene product in the market. The vitamin A level in this observation is approximately 3,6 higher than shark liver oil product in the market without processing by the observation tool. The technology in the observation uses heating principle from perfect black tool that causes it more constantly hot and causes oil flow out from shark liver organ. The oil in the bowl of the tool was filtered by zeolit, so that the unpleasant or fishy smell of the oil will decrease if compared with traditional production process.Keywords : Squalene, vitamin A, Shark liver oil, Cilacap